PEMBELAJARAN TARI KREASI BARU DI PADEPOKAN SENI BAGONG KUSSUDIARDJA YOGYAKARTA - Wien Pudji Priyanto DP (Jurnal Cakrawala Pendidikan, 2005)
AbstractThis article is based on a research conducted to reveal the model, characteristic, and method of the teaching of newly-created dances at Padepokan Seni Bagong Kussudiardja (or PSBK, for short).Employing a naturalistic approach, the research focussed on the teaching of newly-created dances and especially the teaching model used. The data were obtained through observations, interviews, and documentation conducted on the management, teachers, students, and administration staff at PSBK. The instruments for data collection were observation guides, interview guides, and documents. The collection of data involved the use of a tape recorder, writing implements, notebooks,cassette tapes, and a camera for taking photographs. A purposive sample of 14 informants was obtained, consisting of 1 member of the management, 2 members of the administration staff, 7 of the teachers, and 4 of the students. The data obtained were analyzed by means of a descriptive-qualitative method while data validation was done through a triangulation technique.The research result indicates that the teaching of newly-created dances at PSBK is carried out by using a specific system called padepokanand a specific model called pencantrikan. The padepokan system integrates into one the educational system of pesantren (traditional Islamic educational institution in Indonesia), Javanese culture, and the santiniketan model from India. The pencantrikan model integrates into one the characteristics of the social interaction, personal, informationprocessing, and behaviorist models of teaching. The ideas of the specific system and model of teaching are all derived from Javanese cultural concepts identifiable through such terms as padepokan, cantrik, mentrik, wirapertiwi, bhayangkari, gadjah mada, kuda-kuda, yapong, layang-layang, and diponegoro.Key words: teaching newly-created dances, padepokan, cantrik, teachingmodel